ANALYSIS OF ENGLISH CLAUSE PATTERNS: (A Qualitative Analytical on Clause Pattern in Novel) - Helmie, Jauhar; Kurniawati, Nia; Waroka, Tia Siti (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2022)
This research entitled Analysis of English Clause Patterns: A Qualitative Analytical on Clause Pattern in Novel. The aim of this research is to give an explanation in syntactic analysis of the three clause patterns and to give an explanation of each of them in â€Fox Evilâ€novel by Minette Walters. Clauses can be categorized by the verb used in it. There are two verbs, transitive and intransitive verb. Transitive verb devided into two, monotransitive verb is verb has only one object that called as direct object and ditransitive verb has two objects namely direct object and indirect object. The method that the researcher used in this research is descriptive qualitative as its method to analyze and describe entire data. The data are taken from â€œFox Evilâ€ novel by Minette Walters. After getting the data, the researcher analyzed it syntactically. In addition, it is able to be concluded this research those sentence that using transitive verb can analyze based on syntactic unit perspective. Based on the data findings, the writer found that there are 30 data, those are analyzed syntactically based on the clause patterns. The entire three clause patterns were found in the novel fox evil, with details: clause pattern S + V + O as much as 10 data (33,3%), clause pattern S + V + C as much as 10 data (33,3%), clause pattern S + V + AD as much as 10 data (33,3%).